2018
DOI: 10.14814/phy2.13789
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin supplementation mitigates NASH development and progression in female Wistar rats

Abstract: Curcumin, a naturally occurring plant polyphenolic compound, may have beneficial effects in nonalcoholic steatohepatitis (NASH) development. We examined whether curcumin supplementation could be used in both prevention and treatment of NASH with fibrosis. Female Wistar rats were provided ad libitum access to a “western diet” (WD) high in fat (43% kcal), sucrose (29% kcal), and cholesterol (2% w/v), as well as 15% fructose drinking water. Intraperitoneal CC14 injections (0.5 mL/kg) were also administered at wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 45 publications
(48 reference statements)
4
37
0
Order By: Relevance
“…It has been reported that the prevalence of NAFLD rise to 50% in patients with dyslipidemia and to 90% in diabetic patients . The association between NAFLD and metabolic syndrome and thus with obesity, insulin resistance, impaired glucose tolerance, dyslipidemia, and ultimately, increased risk of morbidity and mortality related to the liver and cardiovascular disease (CVD), have been reported by several studies . Pathogenesis of NAFLD is complex and is incompletely understood but it has been reported that it is a reversible condition .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the prevalence of NAFLD rise to 50% in patients with dyslipidemia and to 90% in diabetic patients . The association between NAFLD and metabolic syndrome and thus with obesity, insulin resistance, impaired glucose tolerance, dyslipidemia, and ultimately, increased risk of morbidity and mortality related to the liver and cardiovascular disease (CVD), have been reported by several studies . Pathogenesis of NAFLD is complex and is incompletely understood but it has been reported that it is a reversible condition .…”
Section: Introductionmentioning
confidence: 99%
“…2 The association between NAFLD and metabolic syndrome and thus with obesity, insulin resistance, impaired glucose tolerance, dyslipidemia, and ultimately, increased risk of morbidity and mortality related to the liver and cardiovascular disease (CVD), have been reported by several studies. 1,3,[5][6][7][8][9] Pathogenesis of NAFLD is complex and is incompletely understood but it has been reported that it is a reversible condition. 4,10 However, there are no efficient and accessible FDA-approved pharmacological treatments for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of direct hepatocyte injury releases such markers into the bloodstream and indicates the abnormality of the liver and is noticed to be elevated in rats fed with the MCD diet (Hadizadeh et al, ). The co‐ and pre‐administration of the nutrient mixture to steatosis rats resulted in the decrease of all of these markers, indicating the role of the nutrient mixture as a hepatoprotective agent by reducing the damage done to the hepatocytes by other metabolic factors (Cunningham et al, ; Kargulewicz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence also suggests that curcumin may have anti-steatotic [10] and anti-fibrotic effects on the liver [11, 12]. To this end, we recently evaluated the prophylactic and therapeutic potential of a turmeric extract/curcumin supplement, BCM-95 ® , in a rat model of NAFLD/NASH [13]. In that study/model, we found that curcumin supplementation was partially effective in preventing the development of liver disease and more effective in mitigating its progression.…”
Section: Introductionmentioning
confidence: 99%